KEBIJAKAN EKONOMI POLITIK INDONESIA MENGHADAPI KRISIS KEUANGAN GLOBAL TAHUN 2010-2016 - Laras Seruni Utami; Faisyal Rani (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
This present research describes the politics and economics policy of Indonesia toward global economic crisis in 2010-2016. Global economic crisis was happened since 2008 when economic crisis in United States of America. The crisis in United States of America have impact for the world and one of the states that have impacts are Indonesia. Inflations and good price in Indonesia was influenced by this crisis.The research method used was a qualitative with descriptive as a technic of the research. Writer collects data from books, encyclopedia, journal, mass media and websites to analyze the politics and economics policy of Indonesia toward global economic crisis. The theories applied in this research are merchantilism perspective with the decision making theory by Richard Snyder about foreign analyze factors.The conclusion of the research that the politics and economics policy of Indonesia toward global economic crisis are have done by some policy. In economics scope the policy of Indonesia are have done a moneter policies like moneter stimulations, banking system and balance payment. And in politics policy were done by some policy likes tax allowance and tax amnesty policy and free vissa policy.Key words: policy, economics, politics and global crisis